On the Protestant Foundations of Modern Western Political Thought - CHENG , Bo (Journal of Research for Christianity in China (JRCC), 2025)
The essential difference between Protestantism and Catholicism lies in the opposition between the gospel paradigm and the law paradigm pioneered by Luther. The essence of the gospel paradigm is gospel freedom grounded in theological autonomy. Under the banner of gospel freedom, Protestant ideology attained a form of free expression in faith. Thus, as an intermediary link and transitional form between traditional and modern ideologies, the Protestant ideology of the Gospel paradigm pioneered the first step in the modern trend of secularizing Western political thought through its theoretical achievement of separating the functions of religion and the Gospel. Through its theoretical development—shifting from passive obedience to revolutionary consciousness of active resistance, and transforming from the duty to resist to the right to resist— Calvinism further advanced and facilitated the modern secular turn in Western political thought through the radical development of evangelical liberty. Thus, the evangelical paradigm of Protestant political theology and Calvinism’s radical political thought together form a crucial theoretical foundation of modern Western political thought.